Case Study on Separation Anxiety in an Early Childhood Who Refuses to Go to School - Marzuqi, Muh Syafiq; Hamidah, Hamidah; Saferince , Maria; Irawan, Eka Setyawati; Majid, Andreas (International Journal of Business, Law, and Education, 2025)
Separation anxiety is a typical emotional response in early childhood, particularly during the initial transition to formal schooling. This study aims to explore the forms, contributing factors, and practical mentoring approaches related to separation anxiety in a 4-year-old child who refused to go to school. Using a qualitative approach with a case study design, data were collected through participatory observation during the separation process and classroom activities, semi-structured interviews with parents and teachers, play-based interviews with the child, and supporting documentation. The findings indicate that the child’s separation anxiety manifested specifically during the moment of separation from the mother, characterized by crying, clinging behavior, verbal refusal, and expressions of fear. However, the anxiety gradually subsided after the child engaged in play and felt secure in the classroom. The main contributing factors included a strong attachment to the mother, overprotective parenting practices, limited prior social experience, parental anxiety, and a history of early caregiving trauma that influenced the child’s internal working model. Importantly, the anxiety observed was situational, adaptive, and temporary rather than a clinical disorder. Empathic, consistent, and play-based approaches implemented by teachers were effective in supporting emotional regulation and facilitating adaptation. These findings underscore the importance of collaborative efforts between parents and educators in providing emotionally supportive and developmentally appropriate transition strategies for young children entering school.